2008
DOI: 10.1088/1468-6996/9/4/044206
|View full text |Cite
|
Sign up to set email alerts
|

Two-gap superconductivity inR2Fe3Si5(R=Lu, Sc) and Sc5Ir4Si10

Abstract: R 2 Fe 3 Si 5 (R = Sc, Y, Lu) contains nonmagnetic iron and has a relatively high superconducting transition temperature T c among iron-containing superconductors. An anomalous temperature dependence of specific heat C(T) has been reported for polycrystalline samples down to 1 K. We have grown R 2 Fe 3 Si 5 single crystals, confirmed the anomalous C(T) dependence, and found a second drop in specific heat below 1 K. In Lu 2 Fe 3 Si 5 , we can reproduce C(T) below T c , assuming two distinct energy gaps 2 1 /k B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…The anisotropy of their superconducting properties, anomalous upper critical fields (in Lu2Fe3Si5), and inter-band electron scattering in the case of two weak-coupled distinct gaps opened on the whole Fermi surface (FS) sheets, indicated that they are rather quasi-2D superconductors [26][27][28][29]. Furthermore, some recent works [30][31][32] focused on the effect of doping by non-magnetic impurities and atomic disorder induced by the neutron irradiation, both causing a fast suppression of TC in Lu2Fe3Si5, have questioned the conventional (phononic) mechanism of SC in the (Lu;Y;Sc)2Fe3Si5 family, revealing the significance of spin fluctuations in formation of the SC state [32].…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropy of their superconducting properties, anomalous upper critical fields (in Lu2Fe3Si5), and inter-band electron scattering in the case of two weak-coupled distinct gaps opened on the whole Fermi surface (FS) sheets, indicated that they are rather quasi-2D superconductors [26][27][28][29]. Furthermore, some recent works [30][31][32] focused on the effect of doping by non-magnetic impurities and atomic disorder induced by the neutron irradiation, both causing a fast suppression of TC in Lu2Fe3Si5, have questioned the conventional (phononic) mechanism of SC in the (Lu;Y;Sc)2Fe3Si5 family, revealing the significance of spin fluctuations in formation of the SC state [32].…”
Section: Introductionmentioning
confidence: 99%
“…where ( The two-gap model, which has been proved correct for another intermetallic compound Lu 2 Fe 3 Si 5 9) and may be applicable also in Sc 5 Ir 4 Si 10 , 12) contains two distinct gaps, . For the anisotropic s-wave, the gap structure can be expressed by , corresponding to the gap anisotropy min max / Δ Δ of 0.53±0.04, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, as far as we know little effort has been done on this issue. Tamegai et al 12) suggested that Sc 5 Ir 4 Si 10 may be a two-gap superconductor or only with weak gap anisotropy, while the intrinsic pairing mechanism and gap structure are still unknown.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…In this period, superconductors with various attractive features have been discovered, such as the first heavy fermion superconductor (CeCu 2 Si 2 [2]), multigap superconductors (Lu 2 Fe 3 Si 5 [3,4] and Sc 5 Ir 4 Si 10 [5,4]) and a noncentrosymmetric superconductor (LaPtSi [6,1,7,8]). Reflecting these successful results, the efforts for searching new superconductors in R x T y Si z still have been continued until now.…”
Section: Introductionmentioning
confidence: 99%